O vício secreto: o perigo do despotismo na filosofia de Montesquieu - Patricia Carvalho Reis (2010)
This work aimed to analyse the despotic regime in the thought of Montesquieu. Throughout this research, we try to show that the despotic regime is easier to be accomplished than the moderate regimes. This occurs because of the fact that the despotism needs few requirements to be established, that is, this kind of government does not require the presence of education nor the idea of moderation. Furthermore, another point that favors the easy introduction of despotism in society refers to the fact that the man always searches for more power. Individuals only cease to search for more power if there are outer limits that bar this human beings desire. On the other hand, the existence of moderate regimes depends on the education of citizens and a careful distribution of State powers. Thus, following the thought of Montesquieu, we found that the moderate regimes arise after a hard work, while the despotic regime "strikes the eye, as this regime only needs passions, it is a regime easy to be established.